Physiological function of the Pseudomonas putida PpG6 (Pseudomonas oleovorans) alkane hydroxylase: monoterminal oxidation of alkanes and fatty acids. - Nieder, M (1975)
Pseudomonas putida PpG6 is able to utilize purified n-alkanes of six to ten carbon atoms for growth. It can also grow on the primary terminal oxidation products of these alkanes and on 1-dodecanol but not on the corresponding 2-ketones or 1,6-hexanediol, adipic acid, or pimelic acid. Revertible point mutants can be isolated which have simultaneously lost the ability to grow on all five n-alkane growth substrates but which can still grow on octanol or nonanol. An acetate-negative mutant defective in isocitrate lysase activity is unable to grow on even-numbered alkanes and fatty acids. Analysis of double mutants defective in acetate and propionate or in acetate and glutarate metabolism shows that alkane carbon is assimilated only via acetyl-coenzyme A and propionyl-coenzyme A. These results support the following conclusions: (i) The n-alkane growth specificity of P. putida PpG6 is due to the substrate specificity of whole-cell alkane hydroxylation; (ii) there is a single alkane hydroxylase enzyme complex; (iii) the physiological role of this complex is to initiate the monoterminal oxidation of alkane chains; and (iv) straight-chain fatty acids from butyric through nonanoic are degraded exclusively by beta-oxidation from the carboxyl end of the molecule.